S. Mrożek : Na pełnym morzu - Kabaret Sphincter (Gdańsk : [wydawca nieznany], 1967)
Karta przedstawienia. Na druku: trzy ryby. Reżyseria: W. Wrzesiński; wykonawcy: M, Cieszewski, M. Prus, K. Chęciński, L. Ochyl, T. Lewandowski.
Keywords: Akademia Medyczna (Gdańsk) -- 1945-1970 -- druki ulotne; Kabarety -- Polska -- Gdańsk -- 1945-1970 -- druki ulotne; Studenci -- Polska -- Gdańsk -- 1945-1970 -- druki ulotne; Druki ulotne -- 1945-1970.